Perubahan Wazan, Qafiyah dan Amanat dalam Qasidah Lamiyyah pada Diwan Umru Al-Qais - Silviani, Hopi; Nurlinah; Dayudin (Jurnal Ragam Pengabdian, 2026)
This study aims to examine variations in wazan (meter), patterns of qafiyah (rhyme), and the messages conveyed in the Lāmiyyah Qasidah from the Diwan of Imru’ al-Qais. Classical Arabic poetry is well known for its aesthetic richness, particularly in its rhythmic and rhyming structures, which are central to the disciplines of ‘arūḍ and qawāfī. However, studies that connect these structural features with the meanings embedded in the poems remain limited. Therefore, this research explores the relationship between poetic structure and the ideas expressed in the qasidah. This study employs a qualitative descriptive method using the approaches of ‘arūḍ and qawāfī. The data consist of a Lāmiyyah qasidah comprising 69 verses drawn from three titles. The analysis includes taqṭīʿ al-shiʿr, identification of tafʿīlah patterns, examination of metrical variations such as ziḥāf and ‘illah, analysis of rhyme structures, and interpretation of the conveyed messages. The findings show that the poems employ baḥr ṭawīl, rajaz, and sarīʿ, with several metrical variations, particularly ziḥāf qabḍ, kaff, ṭayy, khaban, and the ‘illah of kasf. The rhyme remains consistent with the letter “lām” as the rawiyy. The poems convey themes of transience, longing, victory, retribution, and the importance of inner peace as a source of happiness.